2018
DOI: 10.1007/s00540-018-2594-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystalloids and colloids on microcirculation, central venous oxygen saturation, and central venous-to-arterial carbon dioxide gap in a rabbit model of hemorrhagic shock

Abstract: Objective The effects of hydroxyethyl starch (HES) on microcirculation, central venous oxygen saturation (ScvO 2 ), and the central venous-to-arterial carbon dioxide gap (dCO 2 ) are studied in a rabbit model of hemorrhagic shock for elucidating the advantages and drawbacks of resuscitation with HES compared with crystalloids. Methods An ear chamber and sublingual mucosa were used to examine blood vessels by intravital microscopy. Hemorrhagic shock was induced by removing nearly half of the blood volume. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Previous studies have pointed out harmful effects of older generation of HES on the kidneys in various patients [12]. However, recent evidences have shown that a third-generation HES did not contribute to the renal dysfunction in subjects with hemorrhagic shock [6][7][8] and in surgical patients [24,25], it preserved renal function through maintenance of microvascular oxygenation [6,26].…”
Section: Clinical Concerns On Fluid Resuscitation With Hes In Acute Hmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have pointed out harmful effects of older generation of HES on the kidneys in various patients [12]. However, recent evidences have shown that a third-generation HES did not contribute to the renal dysfunction in subjects with hemorrhagic shock [6][7][8] and in surgical patients [24,25], it preserved renal function through maintenance of microvascular oxygenation [6,26].…”
Section: Clinical Concerns On Fluid Resuscitation With Hes In Acute Hmentioning
confidence: 99%
“…However, the use of FFP may be limited in emergent situations since it can cause several adverse effects [23]. Recent studies have shown that fluid resuscitation with a third-generation HES (HES 130/0.4) in acute hemorrhagic shock can preserve micro-vessel integrity [8] and protect the glycocalyx layer, leading to better outcomes in animal models of acute hemorrhage [9]. Komori et al have demonstrated that fluid resuscitation with HES 130/0.4 effectively maintained adequate tissue oxygenation and peripheral perfusion compared to that with crystalloids in a rabbit model of hemorrhagic shock [8].…”
Section: Fluid Resuscitation Focusing On Vascular Permeability and Thmentioning
confidence: 99%
See 3 more Smart Citations